Understanding Consumer Adoption And Security Of Internet Banking: A Proposed Biometrics Technology Implementation In The Malaysian Banking Context - Kassim, Normalini Md (2013)
A good human resource decision is based on a good human resource information system (HRIS) which should be provided to both human resource and line managers to facilitate decision making. A HRIS is made up of numerous elements. Each element must function properly if the system is going to benefit the organization. Basically, a system is a set of activities that takes inputs, transforms them into outputs. The special function of HRIS is to gather, collect, and help analyze the data necessary for the human resource department to do its job properly. A good understanding of the factors influencing user adoption the extent use of HRIS and the outcomes that impact human resource (HR) job roles is therefore critical in ensuring the HRIS usage is helping human resource. This study presents the benefits from a survey of 70 HR professional on perceived of innovations factors influencing the extent use of HRIS and to examine the outcomes factors by extensive use of HRIS. Findings revealed that visibility is the attribute of perceived of innovations that influence users extent use of HRIS. There are five outcomes factors by extensive use of HRIS. There are enable information responsiveness, enable information autonomy, enable external professional link, time required on transformational activities and time required on IT support activities. This study also discussed implications of the findings and future research recommendations.